Implementasi Pasal 480 KUHP terhadap Peran Pembeli Barang Hasil Kejahatan Sebuah Tinjauan dari Praktik Persidangan - Ulfa Fatimah; Alex Prayoga Sidabutar; Jihan Aisyah Ramahdania; Dorlince O Hutapea; Parlaungan G Siahaan; Dewi Pika Lbn Batu (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The crime of receiving stolen goods, as regulated in Article 480 of the Criminal Code (KUHP), is an offence that plays a crucial role in the continuation of the principal crime, particularly theft. Receivers provide a market for stolen goods, thereby indirectly encouraging perpetrators to continue their actions. This paper investigates how Article 480 of the KUHP in judicial practice, with a focus on proving the element of ‘knowing or reasonably suspecting’ that the goods purchased were obtained through criminal activity. This study uses a qualitative method with a case study approach through direct observation of a trial at the M. District Court. The observations show that the panel of judges successfully proved the defendant's guilt as a fence through a series of trial facts, such as the unreasonable purchase price, consistent testimony from the perpetrator of the theft, and the defendant's own admission that he had been suspicious. The judge's decision, which was lighter than the prosecutor's demands, also reflected considerations of substantive justice and humanity in addition to legal certainty. This study concludes that the effective enforcement of Article 480 of the Criminal Code in court plays an important role in breaking the chain of crime and providing a deterrent effect not only for the main perpetrators but also for those who participate in enjoying the proceeds of crime.